Community-Based Health Education for Infectious Disease Prevention in Ulu Bawang Barat District - Moh. Solehuddin (Yayasan Adra Karima Hubbi, 2024)
Backgroud. The prevalence of infectious diseases remains a pressing public health concern in rural areas of Indonesia, including Ulu Bawang Barat District, where limited access to healthcare services and low health literacy contribute to continued vulnerability. Conventional health interventions often fail to produce sustained behavioral change due to their top-down nature and lack of cultural sensitivity. Purpose. This study aims to evaluate the effectiveness of a community-based health education model in promoting awareness and prevention of infectious diseases among local populations.Method. A qualitative research approach was adopted using a participatory action research (PAR) design. Data were collected through focus group discussions, semi-structured interviews with community health volunteers and residents, and direct observation of educational activities. Results. The findings indicate that culturally adapted health education programs delivered through peer-led initiatives significantly improved knowledge, attitudes, and preventive behaviors related to hygiene, sanitation, and early disease detection. The involvement of community members in designing and implementing interventions enhanced trust, engagement, and sustainability.Conclusions. The study concludes that community-based health education is a viable strategy for empowering rural populations in managing infectious disease risks. This model emphasizes the role of local agency and participatory learning in strengthening grassroots public health systems.